2018
DOI: 10.1002/hbm.24060
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of myelin content‐based human habenula segmentation at 3 Tesla

Abstract: In vivo morphological study of the human habenula, a pair of small epithalamic nuclei adjacent to the dorsomedial thalamus, has recently gained significant interest for its role in reward and aversion processing. However, segmenting the habenula from in vivo magnetic resonance imaging (MRI) is challenging due to the habenula's small size and low anatomical contrast. Although manual and semi-automated habenula segmentation methods have been reported, the test-retest reproducibility of the segmented habenula vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…Because of this pattern, any segmentation that is based primarily on anatomical image contrast may underestimate the voxels located at the ventral medial portion of the Hb. This observation is likely to account for the lower in-vivo Hb volumes reported here and in previous studies ( 46 , 47 , 50 53 ) compared to ex-vivo estimates ( 31 , 46 , 49 ). The volumetric measurements obtained here did not distinguish between the lateral and medial subdivision of the Hb because such distinction was beyond the resolution of our imaging approach.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Because of this pattern, any segmentation that is based primarily on anatomical image contrast may underestimate the voxels located at the ventral medial portion of the Hb. This observation is likely to account for the lower in-vivo Hb volumes reported here and in previous studies ( 46 , 47 , 50 53 ) compared to ex-vivo estimates ( 31 , 46 , 49 ). The volumetric measurements obtained here did not distinguish between the lateral and medial subdivision of the Hb because such distinction was beyond the resolution of our imaging approach.…”
Section: Discussionsupporting
confidence: 43%
“…This is the largest neuroimaging investigation of the in vivo Hb morphology in BD and SCZ implemented using strict quality control criteria and an objective semi-automated segmentation method shown to yield consistent Hb boundary definitions ( 47 ). The results suggest that volumetric case-control differences are small but the variability in Hb volume may be linked to the severity of suicidality both in SCZ and BD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a couple of studies on automated segmentation of the Hb have been reported. The first study performed semi-and fully-automated segmentation in 3T MRI of healthy young adults [14], and the second study performed fully-automated segmentation in children, adolescents, and adults with bipolar disorder and schizophrenia [15]. In the first study, the DSC for binary segmentation reached 0.71 for semi-automated segmentation and 0.69 for fully-automated segmentation, and the DSC of the probability map reached 0.74 for both semi-and fully-automated segmentation [14].…”
Section: Discussionmentioning
confidence: 99%